The impact of female directors' individual characteristics on corporate financial performance : Evidence from China’s a-share listed companies - He, Qian; Salawati, Sahari (AESS Publications, 2025)
This study investigates how the individual traits of female directors influence corporate financial performance in the context of Chinese listed firms. While prior research has largely emphasized the general impact of gender diversity, this paper focuses on specific attributes such as age, education, overseas experience, financial expertise, and professional background to assess their effects on board decisions and market outcomes. Drawing on a large sample of firms, the study adopts a quantitative approach to examine the variability in these traits and their correlation with financial performance indicators. The findings reveal that not all female directors contribute equally; instead, their unique backgrounds play a significant role in shaping strategic decisions and enhancing firm outcomes. Notably, educational diversity, international exposure, and financial skills emerge as key traits linked to stronger financial results. This study shifts the focus from gender representation to the diversity of qualifications and experiences among women directors, providing a more nuanced understanding of board dynamics. The implications are relevant for policymakers and corporate leaders aiming to improve board effectiveness through targeted appointments. The research contributes to the literature on corporate governance by highlighting the strategic value of trait-based diversity and offers insights for optimizing board composition in a competitive global business environment.